Pengaruh Kompetensi, Pelatihan dan Disiplin Kerja Terhadap Kinerja Karyawan pada BUMDes di Kecamatan Maurole Kabupaten Ende - Bernabas Bego; Hyronimus Se; Ernesta Leha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
There are 13 (thirteen) Village-Owned Enterprises (BUMDes) spread across Maurole District, Ende Regency, with complete management including Director, Secretary, and Treasurer. Different Human Resource capabilities impact the management and development of BUMDes. Low competency, lack of training, and low levels of employee discipline cause BUMDes management to not run optimally. The business units run are not in accordance with the wishes of the Community. This article aims to analyze whether the competency possessed affects employee performance, in addition to whether training and work discipline also affect employee performance. The results of the analysis show that competency affects BUMDes employee performance by 0.504, which means that BUMDes employee performance in Maurole District, Ende Regency has increased. Training has an effect of 0.355, explaining that the training process at BUMDes in Maurole District has increased. Work discipline has an effect of 0.444, which means there is an increase in employee work discipline. With the existence of routine training programs, employee competency will increase, thus impacting BUMDes income and Village original income. The importance of local government support to improve human resources in managing village potential.